The Effect of Sustainability Financial Disclosure, Sustainability Governance and Financing In The Sustainable Business Activities Category On The Share Price of Banks Listed On The Indonesia Stock Exchange - Nikita Trinanda Derzhava; Juniati Gunawan (Pelopor Publikasi Akademika, 2023)
This research aims to determine the influence of sustainable financial disclosure, sustainable governance and financing in the category of sustainable business activities on banking share prices listed on the Indonesia Stock Exchange. Based on data processing from 40 banks listed on the Indonesia Stock Exchange, the results showed that sustainable financial disclosure using the GRI FS indicator had a significant positive effect on the share prices of banks listed on the Indonesia Stock Exchange. Meanwhile, sustainability governance does not have a significant effect on the price of banking shares listed on the Indonesia Stock Exchange, and environmental costs do not have a significant effect on the price of banking shares listed on the Indonesia Stock Exchange